WAS JACQUES DUPUIS A NEORAHNERIAN? - O’Collins, Gerald (Asian Horizons, 2013)
In a 1998 review of Jacques Dupuis’ Toward a Christian Theology of Religious Pluralism, Gavin D’Costa argued that “Dupuis is basically a Rahnerian… Theologically, he carries on from where Rahner left off.”1 After Dupuis died in 2004, D’Costa repeated this judgement about Dupuis. When critically examining what he called the “structural inclusivism” of Rahner in Christianity and World Religions, D’Costa introduced Dupuis and named him a “neo-Rahnerian.”2 In writing of interreligious dialogues, D’Costa stated that Dupuis at various points not only paralleled Rahner’s thought but had also “developed” it.